The relationship of perceived organizational support and deviant behavior in the workplace: The mediating effect of affective commitment and the moderating effect of organization-based self-esteem - Oh, Ahra; Park, Kyungkyu; Yong, Hyunju (Korean Journal of Industrial and Organizational Psychology, 2013)
In this study, the effect of perceived organizational support on affective commitment, in order to investigate the effects of perceived organizational support on employees’ deviant behavior in the workplace, is firstly verified. Then the effect of affective commitment on employees’ deviant behavior in the workplace(organizational deviant behavior and interpersonal deviant behavior) is verified. In addition, the mediating role of affective commitment on the relationship between perceived organizational support and deviant behavior is revealed. Organization-based self-esteem as the moderating variable that can strengthen the relationship between affective commitment and deviant behavior is verified. 252 employees were participated in the study and structural equation analysis was employed to examine the hypotheses. The following is a summary of the results. First, affective commitment increases as perceived organizational support increases. In other words, the higher employees’ perception for organizational support are, the higher affective commitment are. Second, deviant behavior in the workplace decreases as affective commitment increases, that is affective commitment have contributed to the decrease in employees’ organizational deviant behavior and interpersonal deviant behavior. Third, affective commitment was empirically verified to have a mediating effect between perceived organizational support and deviant behavior in the workplace. Also, the moderating effect of Organization-based self-esteem was verified in the relationship between affective commitment and interpersonal deviant behavior in the workplace. Based on these findings, it was determined that perceived organizational support is a significant antecedent of affective commitment and perceived organizational support can be recognized as the motive of affective commitment. The exchange between the employee and employer is positively related to employees’ feelings of perceived organizational support and affective commitment to the organization and reciprocation in the form of lower levels of deviant behavior. Therefore, results also revealed that employees’ perceptions of organizational support have an influence on their attitudes and behavior. Our findings emphasize the importance of valuing employees and investing in their well-being in the workplace.